Keberadaan Uang Elektronik Pada Kehidupan Masyarakat - Novi Primita Sari (CV ODIS, 2021)
Indonesia is at war to enter the era of disruption, namely the existence of various technologies that replace human resources in carrying out all activities and aspects of life, one of which is in the economic sector. Digital technology in the economy has changed all forms of human behavior, both micro and macro. Transaction activities are facilitated through the digital economy which has a big impact on the level of public consumption of an item, namely becoming increasingly consumptive. The high level of consumption is expected to be in line with the increase in productivity in all economic sectors, especially industry. The increase in output produced by the industrial sector will have an impact on the growth of Indonesia's GDP rate, which is expected to be in line with the reduction in the number of poor people in the sense that it will increase the welfare of the Indonesian population.